Subtract the sum of 5n^2 -3n -2 and -7n^2 +n+2 from 12n^2 -n +9 ?

1 Answer
Apr 21, 2018

color(brown)(=> -14n^2 -n - 9 " or " color(green)(-(14n^2 + n + 9)

Explanation:

5n^2 - 3n - 2 + (-7n^2 + n + 2), " Adding first two terms"

=>5n^2 - 3n - 2 - 7n^2 + n + 2, " removing bracket"

=>5n^2 - 7n^2 - 3n + n - cancel 2 + cancel 2, " rearranging like terms together"

=>-2n^2 -2n

-2n^2 - 2n - (12n^2 -n + 9, " subtracting the tnird term from the result"

=> - 2n^2 - 2n - 12n^2 + n - 9, " removing bracket"

=> -2n^2 - 12n^2 - 2n + n - 9, " rearranging terms"

color(brown)(=> -14n^2 -n - 9